Analisia Kegagalan Pengajaran Pendidikan Agama Islam secara Klasikal dalam Perspektif Komunikasi Verbal Monologis - Yenny Imro'atul Mufidah (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Implementation of 2013 Curriculum in Indonesia with a scientific approach shows that most learning activities are directly related to communication. This study aims to describe: failure of teaching classical Islamic education in a monological verbal communication perspective. This research is "Digital Library Research" The research data used is secondary data. The data collection technique used by the authors in this study is documentation. Data processing is carried out by conducting study activities, verification and reduction, grouping and systematization, and interpretation or interpretation so that a phenomenon has social, academic, and scientific value. While the data analysis in this study was carried out during and after data collection using descriptive-critical-comparative methods, and content analysis methods. From the results of the analysis concluded that: failure of teaching Islamic religious education classically in the perspective of monological verbal communication is influenced by several factors including 1) Psychological reasons: That there can be some students who can not catch what the teacher said well and there are also some students who have limitations to understand teacher explanations, and some are not able to digest various teacher explanations for too long, or some have various limitations in some of the above aspects, simultaneously, so that the effectiveness of teaching becomes very disturbed. 2) Emotional Reason: That indeed there are students who have limitations in learning participation in Islam because of the form of delivery, either because they are in an angry atmosphere, feel embarrassed because of being humiliated by the teacher, fear or feeling displeased with the teacher delivering the subject of Religious Education Islam. All these emotional symptoms will interfere with the effectiveness of delivering teaching materials from the teacher to students. 3) Cultural Reasons (Culture): namely that among students there are those who have cultural constraints in the communication process, such as weaknesses in understanding various clues, or weaknesses in understanding the symbols used in communication, so that the process of delivering information on Religious Education becomes ineffective. Personal reasons, which can occur if there are students who are personally really not interested in listening to the delivery of Islamic Education teaching materials from the teacher, although many of them like it